Expanding the theoretical base for the dynamics of willingness to communicate - MacIntyre, Peter (Studies in Second Language Learning and Teaching, 2020)
The dynamics underlying willingness to communicate in a second or third language (L2 for short), operating in real time, are affected by a number of intra- and inter-personal processes. L2 communication is a remarkably fluid process, especially considering the wide range of skill levels observed among L2 learners and speakers. Learners often find themselves in a position that requires the use of uncertain L2 skills, be it inside or outside the classroom context. Beyond issues of competencies, which are themselves complex, using an L2 also evokes cultural, political, social, identity, motivational, emotional, pedagogical, and other issues that learners must navigate on-the-fly. The focus of this article will be on the remarkably rapid integration of factors, such as the ones just named whenever a language learner chooses to be a language speaker, that is, when the moment for authentic communication arrives. Communicative events are especially important in understanding the psychology of the L2 learner. Our research group has developed the idiodynamic method to allow examination of an individual’s experience of events on a timescale of a few minutes. Results are describing complex interactions and rapid changes in the psychological conditions that accompany both approaching and avoiding L2 communication. The research takes a new approach to familiar concepts such as motivation, language competence, learning strategies, and so on. By examining willingness to communicate as a dynamic process, new types of research questions and answers are emerging, generating new theory, research methods, and pedagogical approaches applicable both within language classrooms and beyond.